"That Is Not Very American": A Microethnographic Discourse Analysis of a Chinese ESL Learner's Appropriation of Cultural Values at an Art Exhibition. Issue 3 (17th November 2016) - Lee‐Johnson, Yin Lam
Abstract : This article is based on part of the discourse data collected from a 5‐month ethnographic study about how first‐year learners of English as a second language (ESL) socially interact with their native‐speaking peers in a college town in the U.S. Midwest. The data were collected from participant observation at an art exhibition at the research site. The analysis focuses on a video‐recorded event when an ESL learner from China, Joe, had a negotiated meaning‐making opportunity about the cultural values of art appreciation with his native‐speaking friend, Carmen. The data corpus warrants an analytical framework that focuses on the contextualized interpretations of the smallest meaningful units, and thus the researcher employed microethnographic discourse analysis. The findings suggest that local campus communities are the venues where cultural values are contested, negotiated, and appropriated among ESL learners and their native‐speaking peers. The study also shows that microethnographic discourse analysis is an effective tool for revealing the hidden and unmarked cultural constructs such as "what it means to be American."